Analyzing the Relationship between Coastal Geomorphological Features and Coastal Litter Accumulation in Nam Dinh Area - Thi Ngan, Do; Kinh Bac, Dang; Thi Yen, Nguyen; Thi Phuong Nga, Pham (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Coastal litter pollution in Nam Dinh area has become increasingly concerning due to the combined impacts of human activities, coastal economic development, and natural factors such as climate change. This study analyzed the spatial distribution characteristics and composition of coastal litter based on shore types in Nam Dinh and linked coastal geomorphology to litter accumulation. We combined document collection, field survey and sampling, sociological investigation, remote sensing image analysis, Geographic Information System (GIS), and statistical analyses in this study. The amount of litter at the survey sites ranged from 0-5.3kg/m², classified into five levels: very low, low, medium, high, and very high. The litter is concentrated in estuaries,  alluvial banks, and embankments with accretion phenomenon - where the coastal terrain is low-lying and concave, and the current is weak and difficult to access. From a geomorphological perspective, litter is similar to coastal sediments, which can be transported, accumulated, or redistributed under the influence of dynamic processes such as waves, longshore currents, and seabed topography. The main components of litter include plastic, foam, fishing gear, fabric, metal, and organic litter, with two main sources being river flows and fishing/seafood exploitation activities. The study proposes a few coastal litter management solutions such as prioritizing collection areas suitable for each type of shore and increasing the participation of local communities.